Invasive weed (Parthenium hysterophorus) response to chemical and allelopathic extracts at different stages: Parthenium control (SAARC Journal of Agriculture, 2023)
Parthenium hysterophorus L. is a noxious alien invasive weed species rapidly spreading in Bangladesh. P. hysterophorus examined the prospects of using allelopathic extracts during the period of July 2021 to June 2022. Experiments were conducted in the net house at Sher-e-Bangla Agricultural University, in non-cropped areas of Khustia and cropped areas of Chudanga. The net house experiments were laid out in complete randomized design (CRD) and replicated three times separately for each growth stage. Results showed that by using pretilachlor, pendimethalin, bensulfuron methyl + pretilachlor, bensulfuron methyl + acetachlor, oxadiazon, and pyrazosulfuron-ethyl + pretilachlor decreased the seed germination of parthenium at pot bioassay under both puddle and dry sown condition. At rosette stage of parthenium weed, glyphosate and carfentrazone ethyl (5%) + glyphosate with ½, ¾, and full doses gave 100% mortality at three weeks after treatment (WAT). In cropped areas carfentrazone Ethyl (5%) + glyphosate (36%) and quizalofop-p-ethyl resulted in a 100% and 90% mortality rate at 21 DAT. Overall, the efficacy of herbicides was more effective on rosette parthenium than bolted plants. A phytotoxic response to weed growth was induced by aqueous extracts of Oryza sativa L. var. Boteswar, Triticum aestivum L. var. BARI gom-21, Helianthus annus L., Datura metel, Mangifera indica L., Delonix regia, and Acacia nilotica. Delonix regia was the most effective for inhibition of germination (29%). Whereas Datura metel extracts and Oryza sativa var. Boteswar straw extracts significantly reduced root (1.5 mm) and shoot (3.8 mm) length.SAARC J. Agric., 21(1): 239-252 (2023)